Risk Factors for Severe COVID-19 and Hospital Admission in Patients With Inborn Errors of Immunity - Results From a Multicenter Nationwide Study - Milota, Tomas; Sobotkova, Marta; Smetanova, Jitka; Bloomfield, Marketa; Vydlakova, Jana; Chovancova, Zita; Litzman, Jiri; Hakl, Roman; Novak, Jiri; Malkusova, Ivana; Hanzlikova, Jana; Jilek, Dalibor; et al. (Frontiers in Immunology, 2022)
Despite the progress in the understanding how COVID-19 infection may impact immunocompromised patients, the data on inborn errors of immunity (IEI) remain limited and ambiguous. Therefore, we examined the risk of severe infection course and hospital admission in a large cohort of patients with IEI. In this multicenter nationwide retrospective survey-based trial, the demographic, clinical, and laboratory data were collected by investigating physicians from 8 national referral centers for the diagnosis and treatment of IEI using a COVID-19-IEI clinical questionnaire. In total, 81 patients with IEI (including 16 with hereditary angioedema, HAE) and confirmed SARS-CoV-2 infection were enrolled, and were found to have a 2.3-times increased (95%CI: 1.44–3.53) risk ratio for hospital admission and a higher mortality ratio (2.4% vs. 1.7% in the general population). COVID-19 severity was associated with the presence of clinically relevant comorbidities, lymphopenia, and hypogammaglobulinemia, but not with age or BMI. No individuals with HAE developed severe disease, despite a hypothesized increased risk due to perturbed bradykinin metabolism. We also demonstrated a high seroconversion rate in antibody-deficient patients and the safety of anti-spike SARS CoV-2 monoclonal antibodies and convalescent plasma. Thus, IEI except for HAE, represent significant risk factors for a severe COVID-19. Therefore, apart from general risk factors, immune system dysregulation may also be involved in the poor outcomes of COVID-19. Despite the study limitations, our results support the findings from previously published trials.